Metabolomics Analysis of Splenic CD19+ B Cells in Mice Chronically Infected With Echinococcus granulosus sensu lato Protoscoleces - Guo, Yuxin; Xu, Daxiang; Fang, Zheng; Xu, Shiping; Liu, Jiaxi; Xu, Zixuan; Zhou, Jikai; Bu, Zhenzhen; Zhao, Yingyi; He, Jingmei; Yang, Xiaoying; Pan, Wei; et al. (Frontiers in Veterinary Science, 2021)
Background: The larval stages of Echinococcus granulosus (E. granulosus) infection can alter B cell function affecting the host anti-infective immunity, but the underlying mechanism remains unclear. The newly emerging immunometabolism highlights that several metabolites are the key factors to determine the fate of immune cells, which provides a new insight for exploring how larval E. granulosus infection remodels B cell function. The present study investigated the metabolomics profiles of B cells in mice infected with the protoscoleces (PSC) of E. granulosus. Results: Total CD19+ B cells, purified from the spleen of infected mice, showed significantly increased production of TNF-α, IL-6 and IL-10 after exposure to LPS in vitro. Moreover, the mRNA expression of metabolism related enzymes in B cells were remarkably disordered post infection. In addition, the differential metabolites were identified in the B cells after infection. There were 340 differential metabolites (83 up-regulated and 257 down-regulated metabolites) identified in positive ion model, and 216 differential metabolites (97 up-regulated and 119 down-regulated metabolites) identified in negative ion mode. Among which, 64 differential metabolites were annotated, and involved in 68 metabolic pathways, including thyroid hormone synthesis, the metabolic process of glutathione, fructose and mannose, and glycerophospholipid. Furthermore, several differential metabolites were potentially mapped with the remodeling of B cell function. Conclusion: The infection of the larval E. granulosus causes the metabolic reprogramming in the intrinsic B cells of mice, which provides the first evidence for understanding the role and mechanism of B cells in parasite’s anti-infective immunity in the view of immunometabolism.